2020
DOI: 10.1002/2211-5463.12909
|View full text |Cite
|
Sign up to set email alerts
|

TTK regulates proliferation and apoptosis of gastric cancer cells through the Akt‐mTOR pathway

Abstract: TTK (also known as Mps1) is the core component of the spindle assembly checkpoint, which ensures proper distribution of chromosomes to daughter cells to maintain genome integrity and to balance growth and division. However, the function of TTK in tumorigenesis has not been extensively studied, especially in relation to the development of gastric cancer. In this study, survival and tumor recurrence data related to TTK expression level in gastric cancer patients were collected and analyzed. We observed that TTK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…To investigate whether RAE1 could be a therapeutic target, we performed a comprehensive analysis of 276 genes encoding microtubule‐regulating proteins 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 using TCGA data and evaluated their potential efficacy as a therapeutic target. We calculated the fold change in mRNA expression of each gene in tumor tissues compared to normal tissues, the correlation between mRNA expression and DNA copy number, and whether the high expression group was associated with poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether RAE1 could be a therapeutic target, we performed a comprehensive analysis of 276 genes encoding microtubule‐regulating proteins 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 using TCGA data and evaluated their potential efficacy as a therapeutic target. We calculated the fold change in mRNA expression of each gene in tumor tissues compared to normal tissues, the correlation between mRNA expression and DNA copy number, and whether the high expression group was associated with poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…TTK plays an important role in cell division, and its expression is higher in many human malignancies. Silencing of TTK in PCa, gastric and pancreatic cancer cells inhibited cell proliferation, invasion and migration, and increased apoptosis (Kaistha et al, 2014;Chen et al, 2019;Huang et al, 2020). Thus, it suggests that the inhibition of TTK by MS13 treatment may inhibit cell proliferation and induce apoptosis in AIPC cells.…”
Section: Discussionmentioning
confidence: 95%
“…TTK inhibits the PI3K/AKT pathway, and TTK knockdown inhibits the PKCα/ERK signaling pathway in colon cancer [ 20 ]. Huang et al [ 19 ] and Liu et al [ 14 ] found that TTK activates the Akt/mTOR pathway in gastric and liver cancer. All the aforementioned signaling pathways are involved in regulating autophagy; thus, we focused on the regulatory relationship between TTK and autophagy in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%